Back Matter Vol. 2, No. 1, June 2022 - Uktub Journal (The Arabic Education Department Postgraduate Programs, UIN Sultan Maulana Hasanuddin Banten in Partnership with PPJKBA Indonesia, 2022)
Uktub Journal Author Guideline Back Cover